The Effect of Teaching Science Using McCarthy's' Model (4 MAT) on the 8th Grade Students' Retention of Learning in Jordan - Abdelsalam M. Adili (Sultan Qaboos University, 2017)
This study aimed at finding the effect of using McCarthy's' Model (4 MAT) on 8th grade students' retention of learning in Jordan. The subjects of the study consisted of 86 students from the eighth grade from one Zarqa city school in the second semester of the academic year 2014/2015. The sample was divided into two groups: the experimental group which was taught using 4 MAT model, and the control group which learned in the traditional way. To achieve the objectives of the study, a quasi-experimental approach was followed, and the researcher prepared a valid and reliable achievement test which aimed at measuring students' achievement and retention of learning science. The results revealed statistically significant differences in the students' achievement and retention of learning science due to the method of teaching, and in favor of the experimental group which learned by using the 4-MAT model. In the light of the results, the study recommended the invitation of science teachers to use 4 MAT model in their teaching.